PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, KERJASAMA TIM DAN KOMUNIKASI TERHADAP MOTIVASI KERJA KARYAWAN DI PT. AGRICINAL - Indiani, Suci; Onsardi, Onsardi (UM. Bengkulu, 2024)
Employee performance is the result of the work or contribution of employees to an organization or company in quality and quantity in accordance with predetermined standards based on the responsibilities given. Employee performance also influences output, timeframe, and attendance at work, as well as cooperative attitudes and professionalism at work. In order for employees to provide good performance for the company, the company needs to pay attention to what factors affect the performance of an employee. This study aims to analyze the effect of transformational leadership, teamwork, and communication on employee performance at PT. North Bengkulu Agriculture This study uses the entire population as respondents, namely as many as 90 people who are registered as employees of PT. Agricinal. Data was collected through observation, interviews, and questionnaires. The results of the data obtained were analyzed using validity and reliability tests. The analysis technique used is the multiple linear regression analysis technique. A transformational leadership style has a positive and significant effect on employee performance. Teamwork has a positive and significant effect on employee performance. Communication has a positive and significant effect on employee performance. Keywords: Leadership style, Teamwork, Communication, Work motivation,